2021
DOI: 10.1007/jhep09(2021)105
|View full text |Cite
|
Sign up to set email alerts
|

Radio line properties of axion dark matter conversion in neutron stars

Abstract: Axions are well-motivated candidates for dark matter. Recently, much interest has focused on the detection of photons produced by the resonant conversion of axion dark matter in neutron star magnetospheres. Various groups have begun to obtain radio data to search for the signal, however, more work is needed to obtain a robust theory prediction for the corresponding radio lines. In this work we derive detailed properties for the signal, obtaining both the line shape and time-dependence. The principal physical e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 57 publications
0
51
0
Order By: Relevance
“…Renewed interest in this method of axion searches led to fast progress in our understanding of the details of the process [86,[109][110][111][112][113][114]. The conversion process is slightly different for non-relativistic axions: governing linearized equations are altered [86], and conversion occurs in a resonant mode, in a stark contrast to conversion of 'hot' axions, as discussed above.…”
Section: Compact Object As Haloscopesmentioning
confidence: 99%
See 1 more Smart Citation
“…Renewed interest in this method of axion searches led to fast progress in our understanding of the details of the process [86,[109][110][111][112][113][114]. The conversion process is slightly different for non-relativistic axions: governing linearized equations are altered [86], and conversion occurs in a resonant mode, in a stark contrast to conversion of 'hot' axions, as discussed above.…”
Section: Compact Object As Haloscopesmentioning
confidence: 99%
“…The conversion process is slightly different for non-relativistic axions: governing linearized equations are altered [86], and conversion occurs in a resonant mode, in a stark contrast to conversion of 'hot' axions, as discussed above. In addition, plasma effects that influence propagation of EM waves are much more important for the conversion of non-relativistic axions [113,114].…”
Section: Compact Object As Haloscopesmentioning
confidence: 99%
“…Renewed interest to this method of axion searches lead to fast progress in our understanding of the details of the process [86,[109][110][111][112][113][114]. Conversion process is slightly different for non-relativistic axions: governing linearized equations are altered [86], and conversion occurs in a resonant mode, in a stark contrast to conversion of 'hot' axions, as discussed above.…”
Section: Compact Object As Haloscopesmentioning
confidence: 99%
“…Axion masses spanning from 10 − 100 µeV constitute a particularly compelling range of parameter space, as the DM abundance is arguably achieved most naturally for these candidates [8][9][10][11][12][13][14]. Recent work has shown that QCD axions may efficiently convert into photons in the magnetospheres of neutron stars (NSs), generating powerful spectral lines that may be observable using near-future radio telescopes [21][22][23][24][25][26][27][28][29][30][31][32][33]. Axion-like particles (ALPs), arising ubiquitously in String Theory from the compactification of extra dimensions [34,35] and having a comparable phenomenology to the QCD axion, represent a compelling alternative DM candidate with the potential to be observed by radio telescopes today.…”
mentioning
confidence: 99%
“…The axion-photon conversion process in realistic NS magnetospheres (including photon refraction, photon absorption, plasma broadening, the anisotropic response of the medium, General Relativistic effects, etc.) has been described and simulated with increasing complexity in recent years [24,26,[30][31][32]. The signal appears as a narrow radio line at the frequency corresponding to the axion mass.…”
mentioning
confidence: 99%